2022
DOI: 10.3390/life12030380
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lifestyle Intervention, in Addition to Drugs, for Diabetic Kidney Disease with Sarcopenic Obesity

Abstract: Diabetic kidney disease is the leading cause of end-stage renal disease in developing and developed countries. The growing prevalence and clinical challenges of sarcopenic obesity have been associated with the frailty and disability of diabetic kidney disease. It has been reported that insulin resistance, chronic inflammation, enhanced oxidative stress and lipotoxicity contribute to the pathophysiology of muscle loss and visceral fat accumulation. Sarcopenic obesity, which is diagnosed with dual-energy X-ray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…In a literature review, sarcopenic obesity was associated with frailty among older adults [ 45 ], and with the risk of coronary artery disease and all-cause mortality [ 46 , 47 ]. Recent studies have further shown an association between sarcopenic obesity and chronic renal disease, especially in those with diabetes-related renal impairment [ 48 ]. This may explain why insulin resistance, the over-expression of adipokines, and inflammation processes have been associated with obesity and CKD progression [ 49 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a literature review, sarcopenic obesity was associated with frailty among older adults [ 45 ], and with the risk of coronary artery disease and all-cause mortality [ 46 , 47 ]. Recent studies have further shown an association between sarcopenic obesity and chronic renal disease, especially in those with diabetes-related renal impairment [ 48 ]. This may explain why insulin resistance, the over-expression of adipokines, and inflammation processes have been associated with obesity and CKD progression [ 49 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interactions among muscle wasting, obesity and diabetic nephropathy are unclear. Advanced glycosylated end products (AGEs) have been associated with hyperglycemia, muscle wasting, and impaired renal function in vivo and in vitro [ 54 ], In addition, insulin resistance, oxidative stress, inflammation, uremic toxin toxicity, metabolic acidosis, vitamin D deficiency and protein energy wasting occur in patients with diabetic nephropathy, and they also result in muscle loss and abnormal fat deposition in CKD patients [ 48 ]. Taken together, these findings show that it is important to detect and evaluate sarcopenic obesity to allow for the more intensive management of diabetes and renal dysfunction in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is irrefutable that any diet based on restrictions and exclusions of certain foods will induce a possible increase in the risk of mineral deficiencies and electrolyte imbalance. In fact, studies have shown that consuming a low-carbohydrate diet while maintaining a high intake of protein can lead to a disturbance in fluid and electrolytes, which can further cause kidney damage ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2022) полагают, что изменение образа жизни, физическая активность и снижение жировой массы тела с помощью диеты сами по себе приводят к улучшению физической формы и сохранению мышечной массы. На фоне диабетической нефропатии необходимыми являются предотвращение гипергликемии, ранняя диагностика ХБП, своевременное лечение антигипертензивными препаратами, снижающими активность ренинангиотензиновой системы, и контроль уровня холестерина [49].…”
Section: профилактика и лечение соunclassified